High-strength and high-weatherability HDPE film and preparation method thereof

CN122445090BActive Publication Date: 2026-10-23TIANJIN TIANKAIYUAN ADDITIVE TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610942147.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-23
Estimated Expiration
2046-06-29

AI Technical Summary

Technical Problem

然而,HDPE作为非极性聚合物,其分子结构中缺乏可吸收紫外光的官能团,在户外长期使用过程中极易发生光氧化降解

Benefits of technology

通过十二烷基胺对氧化石墨烯进行接枝改性,显著改善了石墨烯与HDPE基体的相容性与分散性;进一步将改性石墨烯与KH550表面处理的纳米二氧化硅通过静电吸附预组装成片-点杂化增强网络,在熔融共混和吹膜过程中形成贯穿薄膜的二维屏障与三维点状增强协同结构,大幅提升了薄膜的拉伸强度、模量和抗冲击性能。同时,复合抗氧剂、受阻胺光稳定剂和紫外线吸收剂构建了多层级抗老化体系,结合石墨烯的导热辅助热扩散以及可选电子束辐照交联处理,使薄膜在长期户外使用中具备优异的抗热氧老化和光氧化降解能力。本发明实现了HDPE薄膜力学性能与耐候性能的同步显著提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of high-strength high-weatherability HDPE film and preparation method thereof, it is related to polyethylene material technical field.The film includes the following components according to weight parts:HDPE matrix 100 parts, modified graphene 0.5~3 parts, surface treatment nano reinforcing filler 1~5 parts, composite antioxidant 0.1~0.5 parts, light stabilizer 0.1~0.5 parts, ultraviolet absorber 0.05~0.3 parts, dispersion compatilizer 2~5 parts, lubricant 0.5~2 parts;The modified graphene is prepared by dodecylamine grafting graphene oxide, and hybrid reinforcing network is formed by electrostatic adsorption with nano-silica whose surface is treated by KH550;When preparing, it is sequentially subjected to liquid phase electrostatic assembly, melt blending granulation, film blowing forming and electron beam irradiation crosslinking.Modified graphene is uniformly dispersed in HDPE, and builds sheet-point synergistic reinforcing network with nano-silica, which improves the tensile strength and impact resistance of the film;Composite antioxidant, light stabilizer, ultraviolet absorber and graphene physical shielding effect form a multilevel weathering system, prolonging the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyethylene materials technology, and more specifically, to a high-strength, high-weather-resistant HDPE film and its preparation method. Background Technology

[0002] High-density polyethylene (HDPE) film, with its excellent mechanical properties, chemical stability, and processing performance, is widely used in packaging materials, agricultural mulch films, building waterproof membranes, photovoltaic module backsheets, and outdoor protective products. However, as a non-polar polymer, HDPE lacks functional groups in its molecular structure that can absorb ultraviolet light, making it highly susceptible to photo-oxidative degradation during long-term outdoor use. Under ultraviolet irradiation, impurities and carbonyl defects in the HDPE molecular chain trigger free radical chain reactions, leading to macromolecular chain breakage, cross-linking, and destruction of the crystalline structure. This ultimately manifests as yellowing, embrittlement, powdering, and a sharp decline in mechanical properties of the film. Furthermore, HDPE's intrinsic mechanical strength is relatively limited, making it difficult to meet higher requirements in applications that need to withstand heavy loads, further restricting its widespread application in high-end fields.

[0003] Existing technologies, such as CN108864528A, disclose a UV-resistant polyethylene material for water-filled barriers. This material utilizes high-density polyethylene, carbon black, modified titanium dioxide, and maleic anhydride-grafted polyolefins to prepare the UV-resistant polyethylene material. However, the calcination steps designed into the preparation process increase the complexity of processing and raise production costs. CN104497385A employs a composite method of graphene and carbon nanotubes, using melt blending to synergistically reinforce and toughen HDPE. However, in this scheme, the graphene is not surface-functionalized, resulting in unsatisfactory dispersion and interfacial bonding strength in the non-polar HDPE matrix, making it difficult to fully utilize the reinforcing potential of the nanofiller.

[0004] Therefore, there is an urgent need to develop a high-strength, high-weather-resistant HDPE film and its preparation method. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a high-strength, high-weather-resistant HDPE film and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A high-strength, high-weather-resistant HDPE film, comprising the following components by weight: 100 parts HDPE matrix, 0.5-3 parts modified graphene, 1-5 parts surface-treated nano-reinforcing filler, 0.1-0.5 parts composite antioxidant, 0.1-0.5 parts light stabilizer, 0.05-0.3 parts ultraviolet absorber, 2-5 parts dispersant compatibilizer, and 0.5-2 parts lubricant; The modified graphene and the surface-treated nano-reinforced filler form a graphene-nanoparticle hybrid reinforcement network through electrostatic adsorption.

[0007] The present invention utilizes a modified graphene and surface-treated nano-reinforced filler to construct a "sheet-point" synergistic reinforcement network within an HDPE matrix. Graphene provides two-dimensional mechanical support, while nanoparticles act as stress dispersion points. The synergy between these two components significantly enhances tensile strength, modulus, and impact resistance compared to pure HDPE or single-filler systems. A multi-layered anti-aging system is formed by combining a composite antioxidant, light stabilizer, and UV absorber, effectively resisting thermo-oxidative aging and photo-oxidative degradation, thus extending outdoor service life. The introduction of long-chain alkyl groups onto the surface of dodecylamine-modified graphene ensures excellent compatibility with the HDPE matrix and prevents graphene agglomeration. Combined with a dispersant compatibilizer, the interfacial bonding between the inorganic filler and the organic matrix is ​​further improved, ensuring full reinforcement effectiveness. The optimized proportions of each component achieve a good balance between mechanical properties, weather resistance, processability, and cost, avoiding excessive sacrifice of one property for another.

[0008] Preferably, the preparation steps of the modified graphene are as follows: Graphene oxide was dispersed in xylene, sonicated for 10-30 min, dodecylamine was added, and the mixture was stirred at 80-110 °C for 24-48 h under nitrogen protection. After centrifugation, washing, and drying, the modified graphene was obtained. The mass ratio of dodecylamine to graphene oxide is 0.5~2:1.

[0009] In the above-described scheme of the present invention, within the specified ratio range, dodecylamine is grafted onto the surface of graphene oxide in sufficient quantity to obtain adequate alkyl chain coverage, thereby maximizing compatibility and dispersion effect with HDPE; at the same time, it avoids the increased cost caused by excessive amine and the negative impact of free amine on matrix properties; in addition, the appropriate grafting density increases the interlayer spacing of graphene sheets, which is beneficial for exfoliation and dispersion in melt blending, while maintaining the intrinsic mechanical properties of graphene.

[0010] Preferably, the composite antioxidant is composed of hindered phenolic antioxidants and phosphite antioxidants, with a mass ratio of 1:1 to 1:2.

[0011] In the above-described scheme of this invention, the hindered phenolic primary antioxidant captures alkoxy radicals, while the phosphite auxiliary antioxidant decomposes hydrogen peroxide. The combination of these two in this specific ratio produces a synergistic effect, significantly prolonging the oxidation induction period. Under melt blending and blown film conditions, it effectively prevents the thermal degradation of HDPE, reducing yellowing and molecular weight loss. The optimized ratio range ensures both initial antioxidant activity and provides continuous, long-lasting protection.

[0012] Preferably, the light stabilizer is a hindered amine light stabilizer (HALS), and the ultraviolet absorber is a benzotriazole or triazine ultraviolet absorber.

[0013] In the above-described scheme of this invention, the ultraviolet absorber converts harmful ultraviolet light into heat energy, reducing photoinitiation; HALS captures alkyl radicals and alkoxy radicals generated during photo-oxidation, interrupting the photo-oxidation chain reaction. The synergistic effect of both greatly delays yellowing, chalking, and degradation of mechanical properties of the film. The benzotriazole / triazine absorber possesses excellent thermal stability and low migration, and combined with the regeneration and recycling characteristics of HALS, it can continuously provide protection during long-term outdoor exposure.

[0014] Preferably, the dispersing compatibilizer is maleic anhydride-grafted polyethylene with a grafting rate of 0.5% to 1.5%.

[0015] In the above-described scheme of this invention, the polyethylene backbone of maleic anhydride-grafted polyethylene is compatible with the HDPE matrix. The maleic anhydride groups can chemically react with or form hydrogen bonds with the hydroxyl / carboxyl groups remaining on the surface of modified graphene and the amino groups on the surface of nanofillers, significantly enhancing the interfacial bonding strength between the filler and the matrix. This excellent interfacial bonding allows external forces to be effectively transferred from the matrix to the graphene and nanoparticles through the PE-g-MAH molecular chains, improving tensile strength and tear resistance. As a macromolecular compatibilizer, PE-g-MAH can coat the filler surface, and the steric hindrance effect prevents secondary agglomeration of graphene and nanoparticles during processing. A grafting rate of 0.5% to 1.5% provides sufficient reaction sites while avoiding molecular weight reduction or gel formation caused by excessive grafting.

[0016] Preferably, the lubricant is one or both of zinc stearate or calcium stearate.

[0017] In the above-described solution of this invention, zinc / calcium stearate provides both internal and external lubrication. Internal lubrication reduces intermolecular friction in the HDPE melt, while external lubrication reduces adhesion between the melt and the metal surface, thus lowering torque and energy consumption. Calcium stearate can also neutralize trace amounts of acidic substances that may be generated during HDPE processing, preventing acidic catalytic degradation. This improves film surface quality, reduces melt fracture, and enhances film surface smoothness and gloss.

[0018] A method for preparing a high-strength, high-weather-resistant HDPE film, the specific steps of which are as follows: S7-1: Disperse nano-silica ultrasonically in an ethanol solution, add silane coupling agent KH550, wherein the mass ratio of silane coupling agent KH550 to nano-silica is 0.05~0.2:1, stir at 60~80℃ for 4~6h, centrifuge, wash and dry to obtain surface-treated nano-reinforced filler; S7-2: Modified graphene is dispersed in deionized water and the pH is adjusted to 8-9 to obtain dispersion A; surface-treated nano-reinforced filler is dispersed in deionized water and the pH is adjusted to 3-5 with acid to obtain dispersion B; dispersion A and dispersion B are mixed and stirred for 2-4 hours, centrifuged, washed and dried to obtain solid C; S7-3: HDPE matrix, solid C, composite antioxidant, light stabilizer, ultraviolet absorber, dispersant compatibilizer, and lubricant are put into a high-speed mixer and mixed for 5-15 minutes. Then, they are added to a twin-screw extruder for melt blending, extrusion, and granulation to obtain masterbatch. S7-4: Add the masterbatch into the hopper of the blown film machine to form a blown film, and then perform electron beam irradiation crosslinking treatment to obtain the high-strength and high-weather-resistant HDPE film.

[0019] The present invention employs a pre-assembly of a graphene-nano SiO2 hybrid structure in a liquid phase via electrostatic adsorption. Through the directional adsorption of modified graphene with opposite charges and surface-treated nano-silica in the liquid phase, a sheet-dot hybrid structure with nanoparticles uniformly loaded on the graphene sheet surface is pre-constructed. This effectively prevents the self-aggregation of the two nanofillers; the graphene sheets are separated by nanoparticles, making stacking difficult, while the nanoparticles are anchored to the sheets, preventing self-aggregation. Secondly, solid C is dispersed as a single unit within the HDPE matrix, avoiding uneven dispersion caused by competitive wetting of the two fillers during direct blending. Furthermore, efficient load transfer is achieved through a multi-level stress transfer path involving the matrix, nanoparticles, graphene, and matrix, resulting in simultaneous improvement in tensile strength and impact toughness. Moreover, the well-organized hybrid network forms a continuous physical shielding layer in the film. Combined with the thermal conductivity of graphene to aid thermal diffusion, and with composite antioxidants and light stabilizers, a multi-level weather-resistant system is formed, significantly extending service life. KH550 treatment imbues the surface of nano-SiO2 with amino groups, which can form covalent or hydrogen bonds with the carboxyl / hydroxyl groups on the graphene surface based on electrostatic adsorption, resulting in a strong interfacial bond.

[0020] Preferably, the melt blending temperature in S7-3 is 170~220℃, and the screw speed of the twin-screw extruder is 150~300rpm.

[0021] In the above-described solution of the present invention, within this temperature range, HDPE is fully melted and good flowability is maintained, while avoiding excessively high temperatures that could lead to thermal degradation of HDPE or premature consumption of antioxidants. This rotational speed range provides sufficient shear force to disperse the hybrid filler, but without excessive shearing that could damage the graphene sheet structure or cause an excessive decrease in molecular weight.

[0022] Preferably, in S7-4, the die temperature for blown film forming is 180~210℃, the blow-up ratio is 2~4, and the traction ratio is 4~8.

[0023] Preferably, the irradiation dose in S7-4 is 10~25 kGy.

[0024] In the above-described scheme of the present invention, HDPE undergoes moderate cross-linking within this dosage range, which further improves the thermal stability, creep resistance, and environmental stress cracking resistance of the film. At the same time, the cross-linked network structure also helps to fix the hybrid network and prevent filler migration.

[0025] Compared with the prior art, the present invention has the following beneficial effects: Grafting graphene oxide with dodecylamine significantly improves the compatibility and dispersibility of graphene with the HDPE matrix. Furthermore, the modified graphene and KH550 surface-treated nano-silica are pre-assembled into a sheet-dot hybrid reinforcement network via electrostatic adsorption. During melt blending and blown film production, a two-dimensional barrier and a three-dimensional dot-like reinforcement synergistic structure are formed throughout the film, significantly improving the tensile strength, modulus, and impact resistance. Simultaneously, a multi-level anti-aging system is constructed using composite antioxidants, hindered amine light stabilizers, and UV absorbers. Combined with the thermally conductive and heat-assisted diffusion of graphene and optional electron beam irradiation crosslinking treatment, the film exhibits excellent resistance to thermo-oxidative aging and photo-oxidative degradation during long-term outdoor use. This invention achieves a simultaneous and significant improvement in the mechanical properties and weather resistance of HDPE films. Detailed Implementation

[0026] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.

[0027] It should be noted that, unless otherwise specified, the present invention does not specifically limit the source of the raw materials used in the following embodiments. Commercially available products or products prepared by conventional preparation methods that are well known to those skilled in the art can be used. Experimental methods that do not specify specific conditions are all conventional methods and conventional conditions well known in the art.

[0028] The raw materials used in the following examples and comparative examples are as follows: HDPE matrix resin: High-density polyethylene, grade DMDA-8008H, purchased from China National Petroleum Corporation Dushanzi Petrochemical Company; Compound antioxidants: The hindered phenolic primary antioxidant is Irganox 1010 (BASF), and the phosphite auxiliary antioxidant is Irgafos 168 (BASF). Light stabilizer: hindered amine light stabilizer Tinuvin 770 (BASF); UV absorber: Benzotriazole UV-326 (BASF); Dispersant compatibilizer: Maleic anhydride-grafted polyethylene (PE-g-MAH), product number P35025, grafting rate 0.9%, purchased from Shanghai Dingfen Chemical Technology Co., Ltd.

[0029] Example 1 The film comprises the following components by weight: 100 parts HDPE matrix, 1.5 parts modified graphene, 2.5 parts surface-treated nano-reinforced filler, 0.3 parts composite antioxidant (Irganox 1010 and Irgafos 168 in a mass ratio of 1:1), 0.3 parts light stabilizer Tinuvin 770, 0.2 parts ultraviolet absorber UV-326, 3.5 parts dispersant compatibilizer PE-g-MAH, and 1.0 part lubricant zinc stearate; The preparation steps of modified graphene are as follows: 1.0 g of graphene oxide was dispersed in 500 mL of xylene and ultrasonically dispersed for 30 min. Dodecylamine was added, with a mass ratio of dodecylamine to graphene oxide of 1.2:1. The mixture was heated to 95 °C under nitrogen protection and stirred at a constant temperature for 36 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The precipitate was washed successively with xylene and anhydrous ethanol, and finally dried in a vacuum drying oven at 60 °C for 24 h to obtain modified graphene.

[0030] The preparation method of the high-strength, high-weather-resistant HDPE film is as follows: S7-1: 5.0 g of nano-silica was ultrasonically dispersed in 200 mL of ethanol solution, silane coupling agent KH550 was added, the mass ratio of KH550 to nano-SiO2 was 0.1:1, the pH was adjusted to 4.5 with glacial acetic acid, the temperature was raised to 70℃, stirred for 5 h, centrifuged and washed with anhydrous ethanol, and vacuum dried at 60℃ for 12 h to obtain modified nano-SiO2; S7-2: Modified graphene was dispersed in deionized water to a concentration of 2 mg / mL, the pH was adjusted to 8.5 with 0.1 M NaOH solution, and ultrasonically dispersed for 30 min to obtain dispersion A; modified nano-SiO2 was dispersed in deionized water to a concentration of 10 mg / mL, the pH was adjusted to 4.0 with 0.1 M HCl solution, and ultrasonically dispersed for 20 min to obtain dispersion B; dispersion B was added dropwise to dispersion A with stirring, and stirring was continued at room temperature for 3 h after the addition was complete; the mixture was centrifuged, washed with deionized water, and vacuum dried at 60℃ for 24 h to obtain solid C; S7-3: Weigh the HDPE matrix resin, solid C, composite antioxidant, light stabilizer, UV absorber, dispersant compatibilizer, and lubricant according to the formula, and mix them in a high-speed mixer for 10 min; add the mixture to a twin-screw extruder for melt blending and granulation. The extruder temperature settings are: Zone 1 170℃, Zone 2 185℃, Zone 3 200℃, Zone 4 210℃, Zone 5 215℃, and die head 210℃. The screw speed is 250 rpm. The extruded strip is cooled by water and granulated to obtain masterbatch. S7-4: The masterbatch is added to the hopper of the blown film machine for blown film forming. The die temperature is 195℃, the blow-up ratio is 3.0, the traction ratio is 6.0, and the screw speed is 60 rpm to obtain a film with a thickness of 50μm. Then the film is sent to an electron beam irradiation device for irradiation treatment in a nitrogen atmosphere with an irradiation dose of 20 kGy to obtain the film.

[0031] Example 2 The only difference between this embodiment and Example 1 is that the film comprises the following components by weight: 100 parts HDPE matrix, 0.5 parts modified graphene, 1 part surface-treated nano-reinforced filler, 0.1 parts composite antioxidant, 0.1 parts light stabilizer Tinuvin 770, 0.05 parts ultraviolet absorber UV-326, 2.0 parts dispersant compatibilizer PE-g-MAH, and 0.5 parts lubricant zinc stearate; the rest are the same as in Example 1.

[0032] Example 3 The only difference between this embodiment and Embodiment 1 is that the film comprises the following components by weight: 100 parts HDPE matrix, 3 parts modified graphene, 5 parts surface-treated nano-reinforced filler, 0.5 parts composite antioxidant, 0.5 parts light stabilizer Tinuvin 770, 0.3 parts ultraviolet absorber UV-326, 5 parts dispersant compatibilizer PE-g-MAH, and 2 parts lubricant zinc stearate; the rest are the same as in Embodiment 1.

[0033] Example 4 The only difference between this embodiment and Embodiment 1 is that the mass ratio of the composite antioxidant Irganox 1010 to Irgafos 168 is 1:1.5; all other aspects are the same as in Embodiment 1.

[0034] Example 5 The only difference between this embodiment and Embodiment 1 is that the mass ratio of the composite antioxidant Irganox 1010 to Irgafos 168 is 1:2; all other aspects are the same as in Embodiment 1.

[0035] Example 6 The only difference between this embodiment and Embodiment 1 is that the irradiation dose in S7-4 is 10 kGy; all other aspects are the same as in Embodiment 1.

[0036] Example 7 The only difference between this embodiment and Embodiment 1 is that the irradiation dose in S7-4 is 15 kGy; all other aspects are the same as in Embodiment 1.

[0037] Example 8 The only difference between this embodiment and Embodiment 1 is that the irradiation dose in S7-4 is 25 kGy; all other aspects are the same as in Embodiment 1.

[0038] Example 9 The only difference between this embodiment and Example 1 is that the mass ratio of dodecylamine to graphene oxide is 0.5:1; all other aspects are the same as in Example 1.

[0039] Example 10 The only difference between this embodiment and Example 1 is that the mass ratio of dodecylamine to graphene oxide is 1:1; all other aspects are the same as in Example 1.

[0040] Example 11 The only difference between this embodiment and Example 1 is that the mass ratio of dodecylamine to graphene oxide is 2:1; all other aspects are the same as in Example 1.

[0041] Comparative Example 1 The only difference between this comparative example and Example 1 is that unmodified graphene oxide is used instead of modified graphene; all other aspects are the same as in Example 1.

[0042] Comparative Example 2 The only difference between this comparative example and Example 1 is that unmodified nano-silica is used instead of modified nano-silica; all other aspects are the same as in Example 1.

[0043] Comparative Example 3 The only difference between this comparative example and Example 1 is that the modified graphene and modified nano-silica are directly melt-blended with other components without undergoing liquid-phase electrostatic assembly; all other aspects are the same as in Example 1.

[0044] Comparative Example 4 The only difference between this comparative example and Example 1 is that no modified nano-silica is added; all other aspects are the same as in Example 1.

[0045] Comparative Example 5 The only difference between this comparative example and Example 1 is that no modified graphene is added; all other aspects are the same as in Example 1.

[0046] Comparative Example 6 The only difference between this comparative example and Example 1 is that electron beam irradiation is not performed in step S7-4; all other aspects are the same as in Example 1.

[0047] Comparative Example 7 The only difference between this comparative example and Example 1 is that the irradiation dose in step S7-4 is 50 kGy; all other aspects are the same as in Example 1.

[0048] Comparative Example 8 The only difference between this comparative example and Example 1 is that the antioxidant used is Irganox 1010; all other aspects are the same as in Example 1.

[0049] Comparative Example 9 The only difference between this comparative example and Example 1 is that the antioxidant used is Irgafos 168; all other aspects are the same as in Example 1.

[0050] Performance testing The tensile strength and elongation at break of the samples were tested according to GB / T 1040.3-2006 standard at a speed of 200 mm / min.

[0051] The impact strength of the dart was tested according to the GB / T 9639.1-2008 standard. The dart head diameter was 38 mm, the drop height was 0.66 m, and the impact mass at 50% breakage was recorded.

[0052] Accelerated photoaging tests were conducted according to GB / T 16422.3-2014 standard, under the following conditions: irradiance intensity 0.51 W / m². 2 @ 340 nm, temperature 65℃, relative humidity 50%, exposure time 2000 h, to test tensile strength retention rate and yellowing index ΔE.

[0053] The data above show that Example 1 significantly outperforms the comparative examples in key indicators such as tensile strength, dart impact, 2000-hour aging retention rate, and yellowing index. Comparative Example 1 has a strength of only 29.5 MPa and a retention rate of only 45.7%, demonstrating that graphene modification is the foundation for achieving good dispersion and reinforcement. Comparative Examples 4 and 5 both have strengths below 34 MPa, confirming that sheet-point synergistic reinforcement is far superior to single fillers. Comparative Example 3's performance is lower than Example 1, illustrating the necessity of pre-assembling modified graphene and modified silica into a hybrid network. Comparative Example 6 has a retention rate of only 62.8%, and Comparative Example 7's elongation drops to 357.9%, establishing 10-25 kGy as the optimal irradiation dose; excessive crosslinking may lead to impaired mechanical toughness. Comparative Examples 8-9 all have significantly lower retention rates than Example 1, demonstrating the synergistic antioxidant effect of the hindered phenol and phosphite combination. In summary, this invention achieves a simultaneous improvement in both high strength and high weather resistance through the synergistic effect of modified graphene-nano SiO2 hybrid network, multi-level anti-aging system, and moderate irradiation crosslinking.

[0054] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention are still within the scope of the present invention.

Claims

1. A high-strength, high-weather-resistant HDPE film, characterized in that, The film comprises the following components by weight: 100 parts HDPE matrix, 0.5-3 parts modified graphene, 1-5 parts surface-treated nano-reinforced filler, 0.1-0.5 parts composite antioxidant, 0.1-0.5 parts light stabilizer, 0.05-0.3 parts ultraviolet absorber, 2-5 parts dispersant compatibilizer, and 0.5-2 parts lubricant; The modified graphene and the surface-treated nano-reinforced filler form a graphene-nanoparticle hybrid reinforcement network through electrostatic adsorption. The preparation steps of the modified graphene are as follows: Graphene oxide was dispersed in xylene, sonicated for 10-30 min, dodecylamine was added, and the mixture was stirred at 80-110 °C for 24-48 h under nitrogen protection. After centrifugation, washing, and drying, the modified graphene was obtained. The mass ratio of dodecylamine to graphene oxide is 0.5~2:

1. The composite antioxidant is composed of hindered phenolic antioxidants and phosphite antioxidants, with a mass ratio of 1:1 to 1:

2. The specific steps of the method for preparing the thin film are as follows: S7-1: Disperse nano-silica ultrasonically in an ethanol solution, add silane coupling agent KH550, wherein the mass ratio of silane coupling agent KH550 to nano-silica is 0.05~0.2:1, stir at 60~80℃ for 4~6h, centrifuge, wash and dry to obtain surface-treated nano-reinforced filler; S7-2: Modified graphene is dispersed in deionized water and the pH is adjusted to 8-9 to obtain dispersion A; surface-treated nano-reinforced filler is dispersed in deionized water and the pH is adjusted to 3-5 with acid to obtain dispersion B; dispersion A and dispersion B are mixed and stirred for 2-4 hours, centrifuged, washed and dried to obtain solid C; S7-3: HDPE matrix, solid C, composite antioxidant, light stabilizer, ultraviolet absorber, dispersant compatibilizer, and lubricant are put into a high-speed mixer and mixed for 5-15 minutes. Then, they are added to a twin-screw extruder for melt blending, extrusion, and granulation to obtain masterbatch. S7-4: Add the masterbatch into the hopper of the blown film machine to form a blown film, and then perform electron beam irradiation crosslinking treatment with an irradiation dose of 10~25 kGy to obtain the high-strength and high-weather-resistant HDPE film.

2. The high-strength, high-weather-resistant HDPE film according to claim 1, characterized in that, The light stabilizer is a hindered amine light stabilizer, and the ultraviolet absorber is a benzotriazole or triazine ultraviolet absorber.

3. The high-strength, high-weather-resistant HDPE film according to claim 1, characterized in that, The dispersing compatibilizer is maleic anhydride-grafted polyethylene with a grafting rate of 0.5% to 1.5%.

4. The high-strength, high-weather-resistant HDPE film according to claim 1, characterized in that, The lubricant is one or both of zinc stearate or calcium stearate.

5. The high-strength, high-weather-resistant HDPE film according to claim 1, characterized in that, The melt blending temperature in S7-3 is 170~220℃, and the screw speed of the twin-screw extruder is 150~300rpm.

6. The high-strength, high-weather-resistant HDPE film according to claim 1, characterized in that, The die temperature for blown film forming in S7-4 is 180~210℃, the blow-up ratio is 2~4, and the traction ratio is 4~8.

Citation Information

Patent Citations

  • Aminated graphene oxide / high-density polyethylane nano composite membrane and preparation method thereof

    CN104497385A

  • Anti-ultraviolet polyethylene material for plastic road barrier

    CN108864528A

  • High-strength and high-weather-resistance HDPE (high-density polyethylene) film and preparation method thereof

    CN122445090A

  • EPP material and tatami mats made from this EPP material

    JP7734389B1